Studi Relevansi Alumni PGPAUD Universitas Negeri Malang dengan Dunia Kerja - Ahmad Samawi; Retno Tri Wulandari; Eny Nur Aisyah (Faculty of Education Universitas Negeri Malang, 2016)
Abstract: Study on Working Relevancy of The PG-PAUD Alumni of State University of Malang.The aim of this research was to describe: (1) the alumni appointment as teacher; (2) the relevant assignment of the alumni; (3) the spread of the alumni, and (4) the guidance to the alumni. This research useda descriptive research design. The results showed that: (a) most of the alumni (88%) have been appointed as teacher in private institution and some others(12%) in public school, with one month of the long period of waiting for a job;(2) all alumni got the job fitting the competency they have (as childhood teacher); (3) the alumni have been evenly spread to all areas; and (4) most of the alumni (72%) have been found a good guidance in acoording to their needs from supervisors, principals, the educational department, and the institution they work.Abstrak: Studi Relevansi Kerja Alumni PG-PAUD Universitas Negeri Malang. Tujuan penelitian ini adalah mendeskripsikan:(1) pengangkatan alumni sebagai guru; (2) relevansi penugasan alumni; (3) persebaran alumni;dan (4) pembinaan alumni sebagai guru. Penelitian ini menggunakan desain penelitian deskriptif. Hasil penelitian menunjukkan bahwa: (1) sebagian besar alumni (88%) telah diangkat sebagai guru PAUD pada yayasan swasta dan sebagian lainnya (12%) diangkat sebagai guru PNS,dengan masa tunggu 1 bulan; (2) semua alumni bekerja sesuai dengan kompetensinya (sebagai guru PAUD); (3) alumni bekerja tersebar merata; dan (4) sebagian besar (72%) alumni memperoleh pembinaan dengan baik sesuai kebutuhan dari para pengawas, kepala sekolah, Dinas Pendidikan, dan yayasan tempat bekerja.